2017
DOI: 10.1523/jneurosci.0098-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Driving Human Motor Cortical Oscillations Leads to Behaviorally Relevant Changes in Local GABAAInhibition: A tACS-TMS Study

Abstract: Beta and gamma oscillations are the dominant oscillatory activity in the human motor cortex (M1). However, their physiological basis and precise functional significance remain poorly understood. Here, we used transcranial magnetic stimulation (TMS) to examine the physiological basis and behavioral relevance of driving beta and gamma oscillatory activity in the human M1 using transcranial alternating current stimulation (tACS). tACS was applied using a sham-controlled crossover design at individualized intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 70 publications
(96 reference statements)
15
98
0
Order By: Relevance
“…We did not observe a modulatory effect on MEPs during or after tACS-TMS stimulation. This finding is in line with other studies reporting no modulatory effects on MEPs during or after tACS over M1 at (individual) beta or other frequencies (Antal et al, 2008;Nowak et al, 2017;Wach et al, 2013). In contrast, yet other studies have reported such modulatory effects (Feurra et al, 2011(Feurra et al, , 2013Schutter & Hortensius, 2011), however their design differed to that of the current study.…”
Section: The Effect Of Tacs At Alpha and Beta Frequency On Corticospisupporting
confidence: 90%
“…We did not observe a modulatory effect on MEPs during or after tACS-TMS stimulation. This finding is in line with other studies reporting no modulatory effects on MEPs during or after tACS over M1 at (individual) beta or other frequencies (Antal et al, 2008;Nowak et al, 2017;Wach et al, 2013). In contrast, yet other studies have reported such modulatory effects (Feurra et al, 2011(Feurra et al, , 2013Schutter & Hortensius, 2011), however their design differed to that of the current study.…”
Section: The Effect Of Tacs At Alpha and Beta Frequency On Corticospisupporting
confidence: 90%
“…It has been suggested that these after effects depend on spike-timing dependent plasticity (STDP), which may be induced by tACS in recurrent M1 networks. However, others have found no beta-tACS induced after effects [21,26].…”
Section: Introductionmentioning
confidence: 95%
“…TACS studies have tested the idea that entrainment of beta oscillations affects neural excitability by measuring motor-evoked potentials (MEP) with single pulse transcranial magnetic stimulation (TMS). Whereas several studies have demonstrated increased MEP amplitudes during beta-tACS [16e20], others have found no effects [21], and in some cases even decreases in MEP amplitudes were found [22]. In addition to online effects, it has recently been suggested that tACS may induce M1 plasticity lasting up to 60 min after intervention [20,23e25].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy controls, gamma band power increases in contralateral primary sensorimotor cortex just before the onset and during movement [37][38][39][40][41][42] . This increase in gamma power has been shown to facilitate movement in studies using transcranial alternation current stimulation (tACS) to artificially increase gamma power over the contralateral primary sensorimotor cortex [43][44][45] .…”
Section: Intervention-induced Changes Related To Paretic Hand Openingmentioning
confidence: 99%
“…Typically, gamma is associated with local intracortical processing, particularly within GABAergic interneuronal circuits 14,15 , with increases in gamma power related to movement associated with decreases in GABAA 44 . However, gamma synchronization is notable usually confined to a small area in the contralateral primary sensorimotor cortex in healthy controls 37,40,46 , rather than bilateral increases in gamma during movement as observed here prior to the intervention.…”
Section: Intervention-induced Changes Related To Paretic Hand Openingmentioning
confidence: 99%